Nivel de conocimiento y autocuidado en los adultos con diabetes mellitus tipo 2 del barrio Chinguilanchi - Mayo Toledo, Jhoanna Mayte (2024)
Diabetes mellitus is one of the main chronic non-communicable diseases, characterized by persistent hyperglycemia, and is accompanied by alterations in carbohydrate, protein and lipid metabolism. It currently represents one of the greatest challenges faced by health systems worldwide, due to its high prevalence over the years, which has led it to be considered as one of the main causes of morbidity and mortality. Self-care in diabetic patients plays a fundamental role in their treatment, since it helps them to have a better metabolic control and to reduce complications associated with the disease. Therefore, the present research was developed with a quantitative approach, descriptive and cross-sectional design, with the objective of determining the level of knowledge and self-care in adults with type 2 diabetes mellitus in the Chinguilanchi neighborhood. Thirty adults with diabetes mellitus type 2 participated, to whom the knowledge questionnaire and the self-care test were applied, with prior informed consent, obtaining as a result that 56.67% have intermediate knowledge of their disease and 26.67% have inadequate knowledge, 76.67% have adequate self-care while 23.33% have inadequate self-care, when establishing the relationship between these two variables it was found that there is a statistically significant relationship. An educational proposal was elaborated to promote self-care in adults with type 2 diabetes mellitus in the neighborhood, with the purpose of expanding knowledge about their disease and promoting self-care practices. Based on the results of this research, it was identified that the levels of knowledge and self-care are related to each other, that is, the higher the level of knowledge, the better the self-care practices that benefit the patient and improve his or her health